Developmental and Germination Studies of the Sugar Palm (Arenga Pinnata Merr.) Seed - Haris, T.Chairun Nisa (1994)
Very little detailed data on the development and germination of the sugar palm seed (Arenga pinnata Merr.) is available. Therefore studies on the two features were conducted. Changes in the physical and physiological characteristics of the fruit and seed during their development from anthesis until 38 months thereafter were elucidated in the first part of the study. The sugar palm fruit and seed were found to develop very slowly, requiring three years to ripen, and physiological maturity of the seeds was attained at 36 months after anthesis. Progressive embryo growth was not observed until 16 months after anthesis and maximum embryo weight was achieved at 30 months. Towards maturity, thickening of endosperm cell walls occurred progressively until it filled almost the entire cell cavity at 36 months after anthesis, resulting in a hard and bony structure of the endosperm, characteristic for many palm species. Biochemical studies on the composition of food reserves in the mature seed revealed that carbohydrate comprises more than 50% of the reserves present, which mainly consists of mannan. The second part of the study was on germination and seedl ing development. It was found that the mature seeds were dormant because no germination was observed during four months at ambient temperature, although Tetrazolium tests showed them to be viable. However, in vitro germination of excised embryos revealed that immature embryos were capable to germinate since they were fully developed at 16 months after anthesis. And after deoperculation, the seeds germinated readily in two weeks. This shows that like many other palm species, the sugar palm seed also has a coat-imposed dormancy, exerted by the tissues which cover the germination pore. Approximately 700 gram force was needed to rupture this structure. The optimum temperature for germination was 35°C, but for continued seedling growth 30°C was optimum. eedling development was of the remote non-li gular type. The radicle and plumule emerged after five and six weeks' germination. Three different structures were observed in the germinating seed, namely the residual endosperm, degraded endosperm and the haustorium which developed from the cotyledon. The haustorium digests the endosperm and translocated hydrolysed reserves to the developing seedling. The activities of two mannan hydrolising enzymes, B-mannosidase and 6-galactosidase were assayed during germination and early seedling development. The highest enzyme activities were observed in the degraded endosperm. The simple sugars detected were sucrose in the residual endosperm, sucrose and mannose in the degraded endosperm, and sucrose, glucose and fructose in the haustorium.